The reception of Cleopatra in the age of mass media - Daugherty, Gregory Neil 1948- (Bloomsbury Academic, 2023)
"This study examines the reception of Cleopatra from the beginning of the 20th century to the present day as it has been reflected in popular culture in the United States of America. Daugherty provides a broad overview of the influence of the Egyptian queen by looking at her presence in film, novels, comics, cartoons, TV shows, music, advertising and toys. The aim of the book is to show the different ways in which the figure of Cleopatra was able to reach a large and non-elite audience. Furthermore, Daugherty makes a study of the reception of Cleopatra during her own lifetime. He begins by looking at her portrayal in the vicious propaganda campaign waged by Octavian against his rival Marc Antony. The consequence was that Cleopatra was left with a tarnished reputation after the civil war. Daugherty's examination of both the historical and contemporary reception of Cleopatra shows the enduring legacy of one of history's most remarkable queens"--
Keywords: Kleopatra -- VII. -- Ägypten, Königin -- v69-v30; Geschichte 1900-2022; Rezeption; Massenmedien; USA; Cleopatra / Queen of Egypt / -30 B.C. / Influence; Cleopatra / Queen of Egypt / -30 B.C. / In mass media; Cleopatra / Queen of Egypt / -30 B.C. / Public opinion; Popular culture / United States / History / 20th century; Popular culture / United States / History / 21st century; Mass media / United States / History / 20th century; Mass media / United States / History / 21st century; Cleopatra / Queen of Egypt / -30 B.C.; Influence (Literary, artistic, etc.); Mass media; Popular culture; Public opinion; United States; 1900-2099; History